Institutional Review of Spectrum of Covid and Post-Covid Central Nervous System Mucormycosis - Sikiligiri Arshiya; Umamaheswara Reddy Venati; Sabarinath Eada; Yarramsetti Madhusudana (Asian Journal of Medical Radiological Research, 2022)
Background: The objective of the study is to describe the various central nervous system imaging findings and manifestations of the mucormycosis. Subjects and Methods: A retrospective analytical observational study was done on 20 individuals who had biopsy /culture proven invasive rhinocerebral mucormycosis. The case records of these patients were reviewed and the MRI images were retrieved from the Picture archiving and communication system and were analyzed. Statistical analysis was performed using descriptive statistics. Results: MRI imaging of 20 patients with exclusive central nervous system was evaluated which showed predominantly cavernous sinus thrombosis in 5 patients, internal carotid artery thrombosis in 4 patients, cerebral infarction in 4 patients, cerebral abscess was noted in 2 patients, in cerebritis in 2 patient, meningitis in 2 patients and subarachnoid hemorrhage in 1 patient. Conclusion: MRI shows a spectrum of findings Sin central nervous system in rhinocerebral mucormycosis. It plays a major role in assessing the route of spread, extent of involvement and complications.